The Effect of Economic Growth, Fiscal Decentralization, Fiscal Stress, and Economic Openness on Regional Inequality - Hanny Tri Putri; Didik Susetyo; Feny Marissa; Sukanto Sukanto (Department of Development Economics, Universitas Sriwijaya, 2022)
Regional inequality is a phenomenon that occurs universally in all countries, regardless of their size and level of development. Regional inequality is basically caused by differences in the content of natural resources and demographic conditions in each region This study aims to determine the effect of economic growth, the degree of fiscal decentralization, fiscal stress, and economic openness on regional inequality between provinces in Sumatra during the 2010-2020 period. The method used in this study is the panel data regression analysis method using the Random Effect Model. The results showed that simultaneously economic growth, degree of fiscal decentralization, fiscal stress and economic openness influenced regional inequality. Partially, economic growth and the degree of fiscal decentralization have a negative but not significant effect on regional inequality, while fiscal stress has a positive but not significant effect on regional inequality, and economic openness has a positive and significant effect on regional inequality. The implication of this research is that local governments need to adopt policies to impose restrictions on exports and imports, such as barriers in the form of quotas or tariffs.